What Are Adverse Events in Mindfulness Meditation? - Dhanesh D. Binda BS; Carol M. Greco PhD; Natalia E. Morone MD, MS (SAGE Publishing, 2022)
Mindfulness meditation has become a successful treatment of both physical and psychosocial ailments over the past decade. Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT) are now implemented in various clinical and hospital settings for the treatment of stress, depression, substance abuse, and chronic pain. However, given mindfulness meditation's exponential rise in popularity, scientific and media reports have called for the evaluation of mindfulness meditation's safety for those who participate in its programs. Studies have described adverse events, such as anxiety and pain, and more severe events like psychosis, that have been associated with mindfulness meditation. However, there has not been a consistent, systematic way to define and report adverse events in meditation randomized control trials. The objective of our viewpoint was to dispel the notion that these emotive feelings and sensations are adverse events due to mindfulness meditation. Instead, they are actually expected reactions involved in the process of achieving the true benefits of mindfulness meditation. For the more severe outcomes of meditation, for example, psychosis and mania, these events are confounded by other factors, such as the intensity and length of the meditative practices as well as psychological stressors and the psychiatric histories of those affected. Comparatively, mindfulness-based programs like MBSR and MBCT are shorter in duration and less intense. They are designed to be adapted to their participants' needs as to not induce pain or panic. Mindfulness meditation teaches its students to learn how to deal with their minds and bodies instead of using maladaptive coping techniques. Thus, we urge that further research in mindfulness meditation consistently use the definition of adverse events as those which lead to severe outcomes or hospitalization.